2008
DOI: 10.1203/pdr.0b013e31816fee45
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Increased Bone Resorption in Neurofibromatosis Type 1 Using Urinary Pyridinium Crosslink Analysis

Abstract: Although neurofibromatosis type 1 (NF1) is a neurocutaneous disorder, skeletal abnormalities such as long-bone dysplasia, scoliosis, sphenoid wing dysplasia, and osteopenia are observed. To investigate the role of bone resorption as a mechanism for the bony abnormalities, we selected urinary pyridinium crosslinks (collagen degradation products excreted in urine) as a measure of bone resorption in NF1. Bone resorption was evaluated by quantitative assessment of the urinary excretion of pyridinium crosslinks [py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…Moreover, biochemical bone resorption parameters, such as desoxypyridonoline crosslinks, were elevated (Supplement Table 1) in the patients, which is in line with a recently published study of 59 children with NF1 [31]. In addition, by measuring the BMDD in NF1 patients, we observed a novel aspect of their skeletal abnormalities, namely decreased overall calcium content because of an increasing amount of bone packets underlying primary mineralization, as well as an eroded pattern of mineralized bone, when compared to the biopsies from healthy control individuals.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, biochemical bone resorption parameters, such as desoxypyridonoline crosslinks, were elevated (Supplement Table 1) in the patients, which is in line with a recently published study of 59 children with NF1 [31]. In addition, by measuring the BMDD in NF1 patients, we observed a novel aspect of their skeletal abnormalities, namely decreased overall calcium content because of an increasing amount of bone packets underlying primary mineralization, as well as an eroded pattern of mineralized bone, when compared to the biopsies from healthy control individuals.…”
Section: Discussionsupporting
confidence: 89%
“…7). The bones of Nf 1 À=À ob mice also exhibited increased osteoclast numbers and bone resorption similar to humans with NF1 [Stevenson et al, 2008]. These in vivo studies indicated that neurofibromin in osteoblasts inhibits collagen synthesis, promotes mineralization, and also regulates osteoclastogenesis by limiting the expression of receptor activator for nuclear factor k B ligand (RANKL), the major osteoblast-derived cytokine promoting the formation of mature osteoclasts.…”
Section: Mouse Models and Pathophysiology Of Nf1mentioning
confidence: 78%
“…This may be related to an inadequate increase in bone remodeling observed by both bone histomorphometry and changes in circulating bone markers [Stevenson et al, 2008;Seitz et al, 2009]. Despite the consensus that children with NF1 present with low BMD, interpretation of these studies is challenging because bone densitometry measures in adult populations cannot be extrapolated to children, for reasons that include confounding of DXA results by growth and differences in fracture epidemiology in children and adolescents .…”
Section: Osteoporosismentioning
confidence: 99%
“…68 -74 The pathogenesis of these bony changes is not understood, 75 but patients with NF1 may have lower than expected serum 25-hydroxyvitamin D concentrations, elevated serum parathyroid hormone levels, and evidence of increased bone resorption. 72,74,76,77 …”
Section: Skeletal Manifestationsmentioning
confidence: 99%